Teaching English Through Online Learning (A Literature Review) - Suputra, Dwi (STKIP AGAMA HINDU SINGARAJA, 2021)
The aim of this study is to investigate the teaching strategy to be implemented on teaching English through online learning. The design of the present study is a literature review design. Related studies about strategies on teaching English through online learning were analyzed in order to be described in present study. The findings of this present study show that teaching through Learning Management System (LMS), video conference, instant messaging, and digital game could be beneficial strategies on teaching English through online learning. Each strategy has its own characteristics to be implemented in certain situation of online learning. Teachers could utilize various ICT applications which support the implementation of these strategies.